Solvent‐Free Powder Synthesis and Thin Film Chemical Vapor Deposition of a Zinc Bipyridyl‐Triazolate Framework. Issue 1 (3rd December 2019) - Stassin, Timothée; Stassen, Ivo; Wauteraerts, Nathalie; Cruz, Alexander John; Kräuter, Marianne; Coclite, Anna Maria; De Vos, Dirk; Ameloot, Rob
Abstract : MAF‐252, a non‐porous crystalline coordination polymer, is obtained from the solvent‐free reaction of ZnO with 3‐(2‐pyridyl)‐5‐(4‐pyridyl)‐1, 2, 4‐triazole. MAF‐252 can be synthesized in powder form and deposited as thin films, starting from ZnO powder and layers, respectively. Chemical vapor deposition (CVD) of MAF‐252 enables conformal and patterned thin films, even on high aspect ratio features. Abstract : Solvent‐free powder synthesis and thin film chemical vapor deposition (CVD) of MAF‐252, a novel non‐porous crystalline coordination polymer obtained from the reaction of ZnO with a vaporized bipyridyl‐triazole linker. The oxide‐to‐MAF conversion results in a remarkably large film thickness expansion and is compatible with microfabrication.